Environmental challenge trials induce a biofluorescent response in the green sea urchin Strongylocentrotus droebachiensis - Thomas Juhasz-Dora; Stein-Kato Lindberg; Philip James; Tor Evensen; Samuel Ortega (Scientific Reports)
Abstract Stress in sea urchins leads to high mortality and economic losses in both the environment and aquaculture. The green sea urchin Strongylocentrotus droebachiensis has been documented emitting complex biofluorescence, yet how this responds to external stressors is unknown. Adult sea urchins (n = 210) were divided between control (n = 30) and experimental groups (n = 180), using three transport variables: out of water, in water at elevated temperatures, (warm-water) and in water at seawater temperature (cold-water). Hyperspectral imaging of external fluorescence and fluorospectrometric analysis on coelomic fluid was measured at five intervals (hour 0,3,6,9,12). External green emissions (∼580 nm) responded to all treatments, peaking at h9. External red emissions (∼680–730 nm) in the cold-water remained low until an h9 peak. The warm water increased emissions at each interval, peaking at h9. The out of water gradually increased, with the highest at h12. The coelomic fluid fluorescence (∼680 nm) was low to nonexistent except in warm-water, whose elevated levels suggest that fluorescent emissions are a measurable byproduct of internal adaptation(s) to stress. Early detection of fluorescent emissions (broken spines, lesions) may prevent economic losses. The observed link between fluorescence and the applied stressors provides a baseline for developing non-invasive technology for improving echinoderm welfare.